The Effect of the Extraordinary Control on the seizures of the Callao Port Terminal, 2020-2023 - Guevara Gómez, Johan Marcelino (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This research study examines the impact of Extraordinary Control Actions (ACE) on seizures at the Arnold Peter Møller-Maersk (APM) Terminals checkpoint. The methodology was quantitative, descriptive-correlational, and non-experimental. The population consisted of 577 monthly incident reports, and a non-probabilistic sample of 211 reports was selected. Data was collected using a data collection form. A Cronbach's alpha of 81.9% was obtained for the reliability of the data collection form, which was validated using a pilot study of 15 reports. The results show that the ex-ante evaluation dimension is associated with seizures, with a Spearman's rank correlation coefficient of 0.543 (p